The Impact of Brand Image and Customer Relationship Management on Customer Value and Customer loyalty - Abbas, Muchlis (Jurnal Manajemen Bisnis, 2023)
This study adopted a survey method and collected cross-sectional data through questionnaires. Purposive sampling was used, i.e. the customers were Muslim and had been customers of Islamic banks in Makassar City for at least two years, resulting in a total of 278 respondents. The data analysis method used for hypothesis testing is structural equation modeling (SEM). The results of this study show that: (1) brand image has a positive and significant impact on customer value, (2) brand image has a positive and significant impact on customer value. Significant impact. Customer loyalty (3) Brand image has a positive and significant impact on customer loyalty through customer value, (4) Customer relationship management (CRM) has a positive and significant impact on customer value, (5) Customer relationship management has a positive and significant impact on customer value. (6) Customer relationship management has a positive and significant impact on customer loyalty through customer value, (7) Customer value has a positive and significant impact on customer loyalty.